University Open to Older People: factors associated with the use of information and communication technologies - Alice Pinheiro Scarponi; Natália Quevedo dos Santos; Denerval Mendez Batista; Milena Ribeiro Mariucio Aranha; Paulo Vitor Suto Aizava; Sônia Maria Marques Gomes Bertolini (Rev Rene)
Objective: to identify the factors associated with the use of information and communication technologies by older students at a University Open to Older People. Methods: this was an analytical, cross-sectional study with 102 participants of both sexes. This was an analytical, cross-sectional study with 102 participants of both sexes. The study collected data from older people via web to characterize the socioeconomic and technological profile through a self-completed questionnaire. Results: the findings of the present study revealed the existence of a significant association between the frequency in higher education and the use of notebook (p=0.021) and smart TV (p=0.031). Additionally, the analysis observed an association between the monthly family income higher than four minimum wages and the use of tablet (p=0.026), smart TV (p=0.006) and printer (p=0.002) by the sample participants. Conclusion: education level and socioeconomic status were some intervening factors in the use of technologies by the older individuals enrolled in a University Open to Older People. Contributions to practice: the study provides information on the profile of older students regarding the main factors associated with the use of information technologies. With this, activities that enable greater integration and motivation of this population can be programmed and offered.